Inventory of practices in the production of lambanog in Liliw, Laguna, Philippines - Labayog, May Lara Bea C. (College of Home Economics, University of the Philippines Diliman, 2022)
Coconut wine, or lambanog is a colorless distilled spirit obtained by distilling naturally fermented coconut sap from the Philippines (PNS/BAFPS 47:2011; Ascan et. al., 2010; Banaag et al,. 2018; Aquino and Persoon, 2011; Velasco, 2013; Gregorio et. al., 2020). It is known for its 40% to 45% alcohol content with its ethanol content ranging from 30% to 40% (Velasco, 2013; Gregorio et. al., 2020). This study was conducted to establish the inventory of practices in the production of lambanog in Liliw, Laguna, Philippines. This study consisted of three interrelated phases which were 1) development of a survey tool and guidelines that examined the process of lambanog production in Liliw, Laguna, Philippines; 2) key informant interviews and the survey of the process of lambanog production in Liliw, Laguna, Philippines; and 3) establishment of baseline information on the production process of lambanog in Liliw, Laguna, Philippines. Eight key informants in Liliw, Laguna, Philippines participated in the study. Relevant Philippine laws and standard, particularly the manual of Department of Science and Technology Industrial Technology Development Institute on quality control during lambanog production and PNS/BAFS 47:2011 were identified as source of information for the development of survey tools. Gaps were identified upon comparing the actual practices of the lambanog distillers and the reported lambanog process practices in the DOST-ITDI lambanog production manual. Gaps in their level of knowledge and actual practices of lambanog producers in Liliw, Laguna, Philippines showed that despite the education on presence of methanol in lambanog, several factors were found such as lack of proper equipment (i.e. temperature gauges, hydrometer) and lack of reference for standard practice hindered them from applying this knowledge.